Lesson Study dalam Pembelajaran Pendidikan Agama Islam di Sekolah Umum - Ahmad Munjin Nasih; Khoirul Adib (Universitas Islam Negeri Mataram, 2008)
Innovation of education always becomes hot topic to be discussed from time to time because the fact shows that conventional learning methods are still used in educational institutions. Teachers are always viewed as experts who totally hold the power to transfer knowledge and give doctrines to students. The time has come to change this condition. Lesson study (LS) may be one of ways to shift such old paradigm. In that way, teachers should open their classes to be observed by anyone involved in learning process and activities. Therefore, teachers will know weaknesses and strengths of their methods. This article examines LS as an alternative model of improving professionalism of PAI teahers. The model can be aplied based on the principles of colleagues and mutual learning in order to establish a learning community through a gradual and cyclics steps.